Evaluation of research in context: a quick scan of an emerging field. Joint report by the Department of Science System Assessment, Rathenau Institute and the ERiC project - Merkx, F; van der Weijden, I; Oostveen, A; van den Besselaar, P; Spaapen, J (Evaluating Research in Context, 2007)
This Quick Scan is work in progress, a first step to collect information about contextual evaluation of research, that is evaluation that regards research in a broad context and includes all relevant output and the interaction of researchers with their social environment. We invite readers to add articles and other literature, methods, topics, conferences etc. and turn this into a joint enterprise. What we plan to do is through the ERiC website (www.eric-project.nl) organize a ‘living’ document – indeed something like the Wikipedia encyclopedia - containing organized information on evaluation, in particular contextual evaluation. We’ll form an editorial board with international members and will update the document regularly, at least four times per year. Next versions will be issued in September and December 2007. Both the ERiC-project and the Science System Assessment Department of the Rathenau Instituut will take responsibility for this